ANALISIS MOTIVASI BELAJAR SISWA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN BLENDED LEARNING SAAT PANDEMI COVID-19 (DESKRIPTIF KUANTITATIF DI SMAN 1 BABADAN PONOROGO) - Sulistyawati, Wiwik; Wahyudi, Wahyudi; Trinuryono, Sabekti (Kadikma, 2022)
The purpose of this study was to analyze students' learning motivation in blended learning in class X MIPA 5 SMAN 1 Babadan during the covid-19 pandemic. The implementation of this research starts on November 9, 2021 – February 8, 2022. This research is a quantitative descriptive study conducted on 38 students of Mathematics and Natural Sciences class 5 students. This study uses a questionnaire based on indicators of learning motivation by Hamzah as a data collection technique. The results obtained from this study are that there are differences in the level of student learning motivation on the indicators of rewards in learning 58.97% with low learning motivation categories, indicators of interesting activities in learning 79.48% with high learning motivation categories, indicators of encouragement and the need for learning is 84.61% with the category of high learning motivation, and the category of learning motivation is very high on the indicators of the existence of hopes and aspirations for the future 94.87%, indicators of the desire and desire to succeed 100% and, indicators of the existence of a good learning environment. conducive 92.30%. The low category on the indicator of appreciation in learning is 58.97% because in blended learning students are required to be able to use communication technology, in this case, a smartphone with an internet network. Students' expertise in using smartphones makes students able to access websites and question-answering applications so that students can immediately get answers to questions without having to work independently or with their abilities. From the description of the research results above, it shows that learning motivation in blended learning in class X MIPA 5 at SMAN 1 Babadan is very high. This is based on the acquisition of the average value of the indicators of student learning motivation of 85.03%